Factors that affect the English language teaching-learning process in Ecuadorian public high schools - Leiton García, Doris Adriana (2013)
This investigation examines factors affecting the English language teaching-learning process in Ecuadorian public high schools. The method of this study is quantitative. The research took place in five Ecuadorian public high schools in San Gabriel. The sample consisted of fifteen teachers from 8th basic education to 3rd years of senior high school. The process of the research involved observing fifteen classes in each public high school, interviewing fifteen teachers, and applying a survey to fifteen students and the same number of educators. To interpret the obtained results, the information gathered through observation forms, surveys, and interviews was analyzed quantitatively. To do this, it was necessary to consider the answers of the interviewed teachers, the responses of students and educators to the applied survey, and the data of the observed classes.